TOXICITY AND BIOACCUMULATION OF LEAD IN Chlorella AND Dunaliella - Muh Muhaemin (JOURNAL OF COASTAL DEVELOPMENT, 2004)
The aim of this research was to observe the effect of body size in micro algae as significant factor responsible to bioaccumulation of Pb. The research was conducted in Balai Budidaya Laut Hanura, South Lampung using micro algae Chlorella and Dunaliella, observing various Pb concentrations in culture medium and dry weight of micro algae to describe their tolerance and sensitivity levels. Pb concentration in culture medium was determined using AAS (Atomic Absorbance Spectrophotometer) and micro algae biomass observed by optical density approach. Effective concentration of Pb as growth inhibitor of Chlorella and Dunaliella was 50 and 150 μg/l. Dunaliella has greater absorption ability than Cholorella. Less bioaccumulation in Dunaliella indicated high tolerance level to Pb. Dunaliella, whose wider cell surface, has a greater bioaccumulation ability than Chlorella..